THE INFLUENCE OF VOCABULARY JOURNAL IN TEACHING STUDENTSâ VOCABULARY MASTERY - Rakhmawati, Dian (JURNAL SMART, 2016)
The aims of this research is to find out the influence of vocabulary journal as media in teaching student vocabulary at the eighth grade students of SMP Al-Fajar. The quantitative method was conducted and this research is a population research, because all the member of population is taken as sample, which consisted of 30 students of eighth grade. To collect the data, the writer used pre-test and post-test, then the vocabulary test was used as the research instrument. To know whether there is an influence, the writer analyzed the data by using paired-sample T-test.The result shows that there is significant influence of vocabulary journal in teaching studentsâ vocabulary mastery.Keywords: Influence, vocabulary journal, studentsâ vocabulary mastery